CYBERDAKWAH SEBAGAI FILTER PENYEBARAN HOAX - Mazaya, Vyki (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2019)
The internet has become an important part of the interactive communication of the Indonesian people. Information exchange is becoming faster with the advancement of information technology because everyone can easily access and share the information they receive. The ease of sharing information on the other hand can have a negative impact if it turns out that the information received is not clarified in advance. There needs to be an effort and awareness from internet users to prevent the spread of hoaxes on the internet, namely cyberdakwah. Cyberdakwah is an amar ma'ruf nahi munkar activity using internet media. Da'iof cyberdakwah needs to master information technology as one of the main weapons because the target of its dakwah is internet users. Da’i of cyberdakwahalso needs to understand netiquette (internet ethics) besides also having to understand the ethics of da'wahbased on Islamic teachings. This is because in exchanging information there are ethics and values that generally become a common agreement even though the rule may not be written.